2004
DOI: 10.1002/ijc.20239
|View full text |Cite
|
Sign up to set email alerts
|

Increased cancer risk of heterozygotes with NBS1 germline mutations in poland

Abstract: It has been suggested based on familial data that Nijmegen breakage syndrome (NBS) heterozygotes have an increased risk of malignant tumors. We found 15 carriers of the 657del5 mutation and 8 carriers of the R215W molecular variant of the NBS1 gene among 1,289 consecutive patients from Central Poland with various cancers and only 10 and 4 such carriers, respectively, in 1,620 controls from this region. Most of the 657del5 mutation carriers were found among patients with melanoma (4/105), non-Hodgkin lymphoma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
98
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 28 publications
3
98
6
Order By: Relevance
“…The association of the 657del5 mutation with increased risk of hematological cancer has been recently shown. 3,5 In our study, we observed only one 657del5 mutation in c-ALL patients (1/134) and one in controls (1/195). Similar results were reported by several authors who failed to detect a significant contribution of the 657del5 mutation to lymphoproliferative disease development among both Slavic populations 5 and non-Slavic populations, such as in Germany 5 or Britain.…”
contrasting
confidence: 42%
See 2 more Smart Citations
“…The association of the 657del5 mutation with increased risk of hematological cancer has been recently shown. 3,5 In our study, we observed only one 657del5 mutation in c-ALL patients (1/134) and one in controls (1/195). Similar results were reported by several authors who failed to detect a significant contribution of the 657del5 mutation to lymphoproliferative disease development among both Slavic populations 5 and non-Slavic populations, such as in Germany 5 or Britain.…”
contrasting
confidence: 42%
“…Although heterozygous carriers of the NBS1 657del5 mutation have been shown to have an increased risk for breast cancer, melanoma, colon and rectum cancer, 3 other studies have found no association between NBS1 gene mutations and Hodgkin's lymphoma or NHL. [4][5][6] In contrast, Varon et al 7 detected several point mutations in the NBS1 gene among 47 patients with childhood acute lymphoblastic leukemia (ALL).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…(21) Recent studies strongly suggest that heterozygous 657del5 mutation carriers have an elevated risk of malignant tumor development, especially of melanoma, (22,23) colon and rectum cancer, (23) prostate cancer,…”
mentioning
confidence: 99%
“…(17) Heterozygous mutations in the NBS1 gene have been described in various groups of cancer patients, for example, patients with acute lymphoblastic leukemia (ALL), (18,19) non-Hodgkin's lymphoma (NHL), (20) and in cancer cell lines. (21) Recent studies strongly suggest that heterozygous 657del5 mutation carriers have an elevated risk of malignant tumor development, especially of melanoma, (22,23) colon and rectum cancer, (23) prostate cancer, (24) ovarian cancer, (25) breast cancer (26,27) and NHL. (28,29) The aim of our research was to assess whether mutations in the NBS1 gene may contribute to the development of larynx cancer (LC) and MPT of the head and neck.…”
mentioning
confidence: 99%